Games for humanitarian logistics and disaster management: a systematic review - Ducatti, Ana Paula Silva; Doneda, Luna Ribeiro Zimmermann Dias Cocus; Lima, Isabela Antunes de Souza; Cazane, Ana Livia; Bertazzo, Tabata Rejane [UNESP]; Brito Junior, Irineu de [UNESP] (Emerald, 2025)
Purpose This study aims to investigate the use of games in humanitarian logistics and disaster management by conducting a systematic review of academic literature to identify trends, gaps and practical contributions over the past decade. Design/methodology/approach The review followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses 2020 protocol and included peer-reviewed articles published between 2014 and 2024 in English. Searches were conducted in Scopus and Web of Science, last updated in January 2025. A total of 59 studies were included, describing 65 games. Data extraction considered disaster phase, type, game genre, mode, platform, application, audience and time interval. Findings Most games focus on disaster response (25), with hydrometeorological events (22) being the most addressed. Digital (39), multiplayer (43) and simulation-based games (40) are predominant. The main application is education and training (33), and most games target professionals (34). A significant increase in publications occurred from 2020 onward. Gaps were identified in games addressing mitigation, reconstruction, social disasters and community engagement. Research limitations/implications The review included only peer-reviewed articles in English indexed in Scopus and Web of Science, excluding games outside academic literature. Game availability and usability were also not verified, suggesting future research should address these gaps. Practical implications The study offers a structured overview and the creation of an online repository (https://jogoshumanitarios.unimar.br) to facilitate access and adoption of games by researchers, developers and practitioners. Social implications By promoting awareness, preparedness and decision-making skills, the use of serious games in humanitarian contexts can enhance disaster resilience and community engagement. Broad adoption may support more inclusive, collaborative and socially responsive crisis management strategies. Originality/value To the best of the authors’ knowledge, this is the first systematic review to map and categorize academic literature on games in humanitarian logistics and disaster management, providing an open-access repository that bridges knowledge gaps and supports more effective and inclusive game development for crisis preparedness.